Changes and differences in school food standards (2010–2021) and free school meal provision during COVID‐19 across the UK: Potential implications for children's diets. Issue 2 (12th May 2022) - McIntyre, Rebecca Louise; Adamson, Ashley J; Nelson, Michael; Woodside, Jayne; Beattie, Shirley; Spence, Suzanne
Abstract: This paper explores changes to school food standards from 2010, free school meal provision during the COVID‐19 pandemic across the UK and potential implications for children's diets. To obtain information on UK school food policies and free school meal provision methods we reviewed several sources including news articles, policy documents and journal articles. School food is an important part of the UK's health agenda and commitment to improving children's diets. Each UK nation has food‐based standards implemented, however, only Scotland and Wales also have nutrient‐based standards. School food standards in each nation have been updated in the last decade. Universal free school meals are available for children in the first 3 years of primary school in England and the first 5 years of primary school in Scotland, with plans announced for implementation of free school meals for all primary schoolchildren in Scotland and Wales. There is a lack of consistent monitoring of school food across the UK nations, and a lack of reporting compliance to the standards. Each nation differed in its response and management of free school meals during COVID‐related school closures. Further, there are issues surrounding the monitoring of the methods to provide free school meal support during school closures. The role of school food has been highlighted during COVID‐19, and with this, there have been calls for a review of free school meal eligibility criteria. The need for improved and consistent monitoring of school food across the UK remains, as does the need to evaluate the impact of school food on children's diets.